Juventudes rurais e política pública: análise do programa bolsa juventude rural e do perfil demográfico dos beneficiários no Rio Grande do Sul - Cardoso, Anderson Denardin (2024)
How is the Rural Youth Grant Program implemented in practice? What is the sociodemographic profile of its beneficiaries? How do two levels of implementers perceive the trajectory and effectiveness of this public policy? This dissertation aims to describe and analyze the implementation of the Rural Youth Grant Program, a public policy designed to support rural youth by encouraging them to remain in rural areas and complete high school. Furthermore, it seeks to describe the sociodemographic profile of the program's beneficiaries, considering variables such as gender, age, education level, and productive projects. These elements are detailed through quantitative and qualitative methods, using documentary, legislative, and normative data, as well as official reports and structured interviews with rural extension workers who act as program implementers.The main findings indicate that the program has low coverage relative to the potential target audience and reveal a gender disparity among beneficiaries, with women representing only 35% of the total. Qualitative analysis shows that rural extension workers play a crucial role in implementing the program, acting as intermediaries between the public policy and its beneficiaries. However, they also face operational, bureaucratic, and political challenges that affect the program's effectiveness.The implications of this study for the field of public policy implementation are significant. Firstly, it contributes to improving the studied public policy by identifying its strengths and weaknesses and suggesting potential improvements. Secondly, it highlights the role of street-level public agents in policy implementation, recognizing their discretion and adaptability to local conditions. Lastly, it demonstrates the importance of using mixed research methods to capture the complexity and dynamics of public policy implementation.